THE EMERGENCE OF NIGER DELTA AGITATION FILMS IN NOLLYWOOD: A CRITICAL ANALYSIS OF SELECTED WORKS - Harold Idaerefaka Fyneface (Social Sciences, Humanities and Education Journal (SHE Journal), 2022)
: The Niger Delta region has for some time been at the forefront of the struggle for resource control in Nigeria. Starting from the pre-colonial times till date, the region has been characteristically known for this problem, with a lot of unprecedented consequences ranging from fights between the restive youths and community heads on the one hand and the Nigerian government and the multinational oil companies on the other. It is the nature of this crisis that some films depict in what this study identifies as "the Niger Delta films." Anchoring it on the parameters of genre theory in film studies, this work critically examines two of such films that deal with Niger Delta issues. It employs a qualitative methodological approach that includes critical analysis of primary and secondary sources, with the hope that its findings and recommendations will help shed more light on the crisis and raise readers' awareness of the struggle.